Global Weak Solutions of the Cauchy Problem to a Hydrodynamic Model for Semiconductors (Journal of Partial Differential Equations, 2020)
In this paper we are concerned with the global existence of weak solutions of the Cauchy problem for a simplified one-dimensional hydrodynamic model for semiconductors. Convergence of approximate solutions derived by the fractional step Lax-Friedrichs scheme is established by using the compensated compactness method.
Keywords: Hydrodynamic model; Lax-Friedrichs scheme; compensated compactness